PENGARUH KINERJA PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK DI BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN MAMUJU UTARA - Bismawati, Bismawati (Katalogis, 2016)
The aim of this study; (1) to determine the competence of the individual, orgnaisasi support, and management support simultaneously (synchronously) significantly affects the quality of public services in the Regional Disaster Management Agency of North Mamuju regency; (2) to determine the competence of the individual partial (people) have a significant effect on the quality of public services in the Regional Disaster Management Agency of North Mamuju regency; (3) to determine orgnaisasi partial support (people) have a significant effect on the quality of public services in the Regional Disaster Management Agency of North Mamuju regency; (4) to determine partial management support (people) have a significant effect on the quality of public services in the Regional Disaster Management Agency of North Mamuju regency. This type of research is descriptive and verification. This study population Tikke Raya subdistrict community numbering 4,039 were drawn using the formula so that the sample size of 98 respondents with proportional random sampling technique. Data collection techniques including observation, questionnaires, and documentation, and data analysis technique multiple linear regression. The results showed; (1) individual competence, orgnaisasi support, and management support simultaneously (synchronously) significantly affects the quality of public services in the Regional Disaster Management Agency of North Mamuju regency. The magnitude of these effects amounted to 89.6% at the level of the relationship between variables "very strong"; (2) Competence partially individuals (people) have a significant effect on the quality of public services in the Regional Disaster Management Agency of North Mamuju regency; (3) Support organization partially (people) have a significant effect on the quality of public services in the Regional Disaster Management Agency of North Mamuju regency; (4) The partial management support (people) have a significant effect on the quality of public services in the Regional Disaster Management Agency of North Mamuju regency.